In-situ and Operando (Scanning) Transmission Electron Microscopy (S)TEM; a real-time investigation of energy storage devices and materials at the atomic level - Ronan, Oskar Henry (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
In the modern age of ubiquitous mobile technology, demand for ever increasing battery capacity and size reduction in such devices is a key driving factor for this sector. Technology is currently striving to improve the power density of batteries and the energy density of supercapacitors. To do so it is imperative to develop new materials, chemistries and manufacturing strategies. However, before all these proposed potential applications can be realised it is crucial to understand the fundamental processes taking place during materials synthesis, processing and device functioning. In real technological applications, a material may in fact be exposed to a variety of stimuli such as mechanical stress, and electric fields. The response of the material to these stimuli often determines their functionality, behaviour and performance in applications. The aim of this work is to develop a detailed description of the materials under scrutiny in their working states and develop an experimental approach which combines advanced microscopy techniques and electrochemical testing using a specialised in-situ liquid-cell holder developed for electron microscopy. This was used to observe and image electrode materials (specifically, Si-based conversion-alloying anode materials) in their working state on the nano-scale. This experimental approach has effectively allowed for a TEM to be used as a "nano-laboratory" for carrying out dynamic electrochemical experiments on a small spatial scale. Furthermore, in addition to observing materials in their working state, in-situ techniques can be used to also capture important intermediate transitional forms, that may be missed by more conventional post-mortem methods. To date, we have successfully printed an electrochemical cell consisting of silicon nanoparticles and LiFePO4, and assemble it for in-situ observation; this technique is still in the early stages of development, and the experimental issues arising from attempting to perform this type of in-situ Transmission Electron Microscopy analysis and solutions are discussed in this work. Transmission Electron Microscopy (TEM), and Scanning Transmission Electron Microscopy (STEM) have proven to be useful tools for such characterization, allowing structure, composition, bonding and spectroscopic imaging to be followed at the atomic level.
APPROVED
Keywords: In-Situ Transmission Electron Microscopy; Electrochemistry; Lithium Ion Battery